2006
DOI: 10.1159/000098131
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Quercetin on Tryptase and MCP-1 Chemokine Release, and Histidine Decarboxylase mRNA Transcription by Human Mast Cell-1 Cell Line

Abstract: Mast cells are important in reactions of allergic disease and are also involved in a variety of neuroinflammatory diseases. Mast cells can be immunologically activated by IgE through their Fc receptors, as well as by neuropeptides and cytokines to secrete mediators. Here we used a human mast cell-1 (HMC-1) cell line cultured and treated with a physiological activator, anti-IgE, and a nonphysiological activator, calcium ionophore A23187, for tryptase and MCP-1 generation and transcription of histidine decarboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…An unpublished analysis by Efficas, Inc. of the phenolic constituents of EFF1001 by HPLC‐UV revealed the presence of the ubiquitous flavonoids quercetin, isorhamnetin, kaempferol, in approximate amounts ranging from 20 to 80 μg/mL. There are numerous reports in the literature on the anti‐inflammatory effects of these and similar flavonoids; 9–12 however, the degree to which these compounds contribute to the overall activity of EFF1001 is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…An unpublished analysis by Efficas, Inc. of the phenolic constituents of EFF1001 by HPLC‐UV revealed the presence of the ubiquitous flavonoids quercetin, isorhamnetin, kaempferol, in approximate amounts ranging from 20 to 80 μg/mL. There are numerous reports in the literature on the anti‐inflammatory effects of these and similar flavonoids; 9–12 however, the degree to which these compounds contribute to the overall activity of EFF1001 is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The cell lines have been characterized one at a time, but their direct relation to normal human tissue MC has remained unknown. Nevertheless, both cell lines are extensively used as surrogates for non-transformed primary human MC (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…They are multifunctional proteins which have a role in both innate and adaptive immune responses (8-13) with an effect on proliferation, differentiation, inhibition, apoptosis and chemoattraction (14-16). In addition, cytokines are involved in and mediate many different diseases (17-18).The newly-characterized Interleukin-34 (IL-34) plays a central role in innate immunity and adaptive immunity, and is an important molecule for the communication between cells, tissues, and organs.Recently it has been reported that interleukin-34 (lL-34) stimulates monocyte viability but does not affect responses in a wide spectrum ofother assays (20)(21)(22)(23)(24)(25). In both in vitro and in vivo studies, IL-34 directly modulates the number and function of monocytes and regulates myeloid cell growth and differentiation.…”
mentioning
confidence: 99%
“…Recently it has been reported that interleukin-34 (lL-34) stimulates monocyte viability but does not affect responses in a wide spectrum ofother assays (20)(21)(22)(23)(24)(25). In both in vitro and in vivo studies, IL-34 directly modulates the number and function of monocytes and regulates myeloid cell growth and differentiation.…”
mentioning
confidence: 99%